On the empirical relevance of the exchange rate as a shock absorber at the zero lower bound - David Finck; Mathias Hoffmann; Patrick Hürtgen (Philipps-University Marburg, School of Business and Economics, 2022)
The open economy New Keynesian model with flexible exchange rates postulates that the real exchange rate appreciates in response to an asymmetric negative demand shock in a zero lower bound (ZLB) scenario and exacerbates the adverse macroeconomic effects. However, when monetary policy is able to accommodate the adverse effects of the negative demand shock via unconventional measures, the model can generate a real depreciation at the ZLB. This paper examines these counteracting exchange rate channels empirically. We estimate the effect of a negative asymmetric demand shock on the real exchange rate and inflation expectations as well as output and prices by employing state-dependent and sign-restricted local projection methods for the euro area vis-\~A -vis the United States, Canada, and Japan. We find that the real exchange rate depreciates when interest rates are not at the ZLB but also when they are. Furthermore, our empirical results show that the real exchange rate can absor considerable variations in output, confirming its shock-absorbing capacity before but also during the ZLB episode. The stabilizing role of the exchange rate is accompanied by a significant expansion of the ECBs balance sheet in the ZLB period, while it remained unaffected in the pre-ZLB period. Overall, our empirical results favor the open economy New Keynesian model with unconventional measures when interest rates are at the ZLB.
Keywords: F31; E31; E37; C54; 330; Zero Lower Bound; Exchange Rate; Local Projections; State-dependent Effects